2020
DOI: 10.1038/s41586-020-2173-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal 15N15N abundances constrain the origins of mantle nitrogen

Abstract: Nitrogen is the main constituent of the Earth's atmosphere, but its provenance in the Earth's mantle remains uncertain. The relative contribution of primordial nitrogen inherited during the Earth's accretion versus that subducted from the Earth's surface is unclear 1-6. Here we show that the mantle may have retained remnants of such primordial nitrogen. We use the rare 15 N 15 N isotopologue of N 2 as a new tracer of air contamination in volcanic gas effusions. By constraining air contamination in gases from I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 91 publications
7
79
1
Order By: Relevance
“…However, a dichotomy seems to exist for nitrogen isotope ( 15 N/ 14 N) ratios, with CC irons being enriched in 15 N compared to NC irons (Scott et al 2018). These observations are consistent with the general trend of increasing 15 N-enrichments with radial distance from the Sun (Füri and Marty 2015), i.e., from the Sun (δ 15 N Sun = -383 ± 8‰; Marty et al 2011) to the Earth-Moon system (δ 15 N Earth-Moon ≈ -40 to +26‰; Palot et al 2012;Cartigny and Marty 2013;Füri et al 2015;Labidi et al 2020) and Mars (δ 15 N Mars,mantle -30‰; Mathew and Marti 2001) and to comets (δ 15 N Comet ≈ +800 to 1000‰; Bockelée-Morvan et al 2015, and references therein). In contrast, nitrogen isotope ratios recorded by chondrites do not display the NC-CC dichotomy.…”
Section: Constraints From Nitrogen Isotopessupporting
confidence: 89%
“…However, a dichotomy seems to exist for nitrogen isotope ( 15 N/ 14 N) ratios, with CC irons being enriched in 15 N compared to NC irons (Scott et al 2018). These observations are consistent with the general trend of increasing 15 N-enrichments with radial distance from the Sun (Füri and Marty 2015), i.e., from the Sun (δ 15 N Sun = -383 ± 8‰; Marty et al 2011) to the Earth-Moon system (δ 15 N Earth-Moon ≈ -40 to +26‰; Palot et al 2012;Cartigny and Marty 2013;Füri et al 2015;Labidi et al 2020) and Mars (δ 15 N Mars,mantle -30‰; Mathew and Marti 2001) and to comets (δ 15 N Comet ≈ +800 to 1000‰; Bockelée-Morvan et al 2015, and references therein). In contrast, nitrogen isotope ratios recorded by chondrites do not display the NC-CC dichotomy.…”
Section: Constraints From Nitrogen Isotopessupporting
confidence: 89%
“…nonthermal site and why the noble gases are less contaminated by atmosphere. The greater mantle volatile contribution in Brimstone Basin has also been further substantiated by a recent innovative study that used the rare 15 N 15 N isotopologue of N 2 to identify and correct for air contamination in volcanic gas emissions (39). This study revealed that not only did the Brimstone Basin samples contain the greatest contribution of mantlederived N 2 of all of the Yellowstone samples measured but also that the δ 15 N of the Yellowstone mantle source is distinct from MORB and in line with previous determinations of plumederived samples (39).…”
mentioning
confidence: 86%
“…The emission rate and isotopic composition suggest that a significant amount of helium has been liberated from the Archean rocks over the past 2 million years since the crust was affected by magmatism (Lowenstern, Evans, et al., 2014). Other studies have shown some of the other noble gases and nitrogen emitted from the YPVF hydrothermal system are derived from the mantle (Broadley et al., 2020; Labidi et al., 2020).…”
Section: The Yellowstone Plateau Volcanic Field Hydrothermal Systemmentioning
confidence: 99%